Theoretical Study at the Molecular Mechanics Level of the Interaction of Tetracycline and Chloramphenicol with the Antibiotic Receptors Present in Enterococcus faecalis (Q839F7) and Streptococcus mutans (Q8DS20) - Rufo Alberto Figueroa-Banda; Kimberly Francis Figueroa-Castellanos; Edith Angelica Chávez-Oblitas; María Elena Guillen-Nuñez; Flor Ayqui-Cueva; Bruno A. Del-; Karen L. Bellido-Vallejo; Badhin Gómez (MDPI AG, 2022)
When dental infections occur, various types of antibiotics are used to combat them. The most common antibiotics to be used are tetracycline and chloramphenicol; likewise, the most common bacteria in dental infections are Enterococcus faecalis and Streptococcus mutans. In the present work, we have studied by molecular mechanics methods the interactions of the ribosomal proteins L16 present in Enterococcus faecalis and Streptococcus mutans, identified with UNIPROT code Q839F7 and Q8DS20, respectively. We evaluated the interactions between Q839F7 and Q8DS20 with tetracycline and chloramphenicol antibiotics. We found that the interaction between Enterococcus faecalis (Q839F7) is much more favorable when treated with chloramphenicol. In contrast, the interaction with tetracycline is favored in the case of Q8DS20 present in Streptococcus mutans. This suggests that the treatment should be differentiated depending on the infection level and the presence of some of these bacteria.